RHIZOTOXICITY OF THE INVASIVE SPECIES MELIA AZEDARACH: IMPLICATION OF PHENOLS ON ITS HERBICIDE POTENTIAL - M. Akacha; K. Lahbib; N. G. Boughanmi (Journal of Animal and Plant Sciences, 2017)
A biological invasion of non-native plants is spreading into our natural areas and rights-of way. In the present work, Melia azedarach (Meliaceae) known for its high allelopathic potential is used to investigate its bio-pesticide capacity on the common model used in bioassays: Raphanus sativus (R. sativus). Exposure of R. sativus to M. azedarach (aqueous/ethanolic) leaves extracts result on toxicity exclusively toward roots. The roots inhibition was dose dependent and more pronounced for ethanolic extract. Allelochemicals of M. azedarach ethanolic extracts induced an oxidative stress in radish focalized by a decrease on enzymatic anti-oxidant defense such superoxide dismutase (SOD) activity. However, the stimulation of phenyl-alanine ammonialyase (PAL) activity and the subsequent increase in phenols content failed to alleviate R. Sativus roots oxidative stress. Importantly, the result of M. azedarach leaves extracts inducing oxidative imbalance in roots seemed to be harmful in vivo on R. sativus but exceeded its antioxidant abilities in vitro. M. azedarach invasive species might be valorized, in Tunisia, by developing “root killers” bio-herbicides and enhancing biological proprieties of received plant.
Keywords: Melia azedarach; raphanus sativus; rhizotoxicity; oxidative stress and bio-herbicide